Prioritizing factors affecting Iranian non-oil export using group decision making approach based on hierarchical analysis process - K. F. Mohammadbeigi; S. Daniali; Y. Mohammadbeiki (Управление)
Iran’s economy has three sectors: hydrocarbons, agriculture and services. Due to the historical trend, Iranian economy is under the influence of government governance in production and services. Considering the role of non-oil exports and the over-reliance of Iranian economy on petroleum and petroleum products, it is necessary to conduct a research to determine the factors, which affect non-oil export.Since oil revenues are not considered as a reliable source of revenue for the government due to their volatility, development of non-oil export is one of the major goals of Iranian most important goals. If the goals, set in this area will be achieved, the country’s position will be improved in terms of foreign exchange, curbing the volatility, caused by oil prices and gaining economic and competitive advantages in the global arena. The most important issue in the development of nonoil exports is the liberalization of economic capacity through new investments.In this article all factors, affecting non-oil exports have been determined, based on studying literature. Considering a survey of 32 executives and experts of Fajre Jam Refining Company as one of the most important condensate exporter companies in the country and region, the most important of them have been identified and then categorized using the affinity graph approach. Pairwise comparisons were used to weight the main and sub-factors with the participation of 10 executives and experts of the mentioned company within the framework of the analytic hierarchy process in expert choice software.